2004
DOI: 10.1016/j.theriogenology.2003.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different cryoprotectants on the structural preservation of follicles in frozen zebu bovine (Bos indicus) ovarian tissue

Abstract: Effect of different cryoprotectants on the structural preservation of follicles in frozen zebu bovine (Bos indicus) ovarian tissueCarolina M Lucci Mirella A Kacinskis Luiz Henrique R Lopes Rodolfo Rumpf Sônia N Báoa AbstractCryopreservation of ovarian tissue is a new and promising technique for germ-line storage. The objective of this study was to evaluate the effect of four cryoprotectants (at two concentrations each) on the preservation of zebu bovine preantral follicles after ovarian cryostorage. Strips of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
44
1
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 26 publications
(59 reference statements)
6
44
1
7
Order By: Relevance
“…Unlike results previously reported in our studies in pigs [23], cattle [30], and sheep [19], DMSO was able to maintain the ultrastructure of preantral follicles enclosed in ovarian tissue after cryopreservation. In follicles included in ovarian tissue that were cryopreserved in the presence of EG, greater damage was observed in this study, manifested as reduced electron density and fewer organelles in the ooplasm.…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike results previously reported in our studies in pigs [23], cattle [30], and sheep [19], DMSO was able to maintain the ultrastructure of preantral follicles enclosed in ovarian tissue after cryopreservation. In follicles included in ovarian tissue that were cryopreserved in the presence of EG, greater damage was observed in this study, manifested as reduced electron density and fewer organelles in the ooplasm.…”
Section: Discussioncontrasting
confidence: 99%
“…While the study by Celestino and colleagues (Celestino et al, 2008) showed increased toxicity with rising concentration of DMSO, the other study (Lucci et al, 2004) showed slightly higher proportion of normal follicles in the 3 M DMSO group when assessed by conventional histology. However, ultrastructural analysis by transmission electron microscopy (TEM) revealed some irregularities in the cytoplasm of granulosa cells when 3 M DMSO was applied (Lucci et al, 2004).…”
Section: Cowmentioning
confidence: 86%
“…The toxic effect of various concentrations and types of CPAs that are frequently used for slow freezing was compared using bovine ovarian cortical strips (Lucci et al, 2004;Celestino et al, 2008). Among other CPAs, DMSO at 1.5 M and 3 M were evaluated in both studies.…”
Section: Cowmentioning
confidence: 99%
“…O transporte de ovários à 4°C possibilitou a preservação dos oócitos, especialmente dos obtidos da fase de diestro, devido aos altos índices de M-II encontrados nesta fase do ciclo estral. Lucci et al (2004) observaram que os ovários de vacas zebuínas puderam ser armazenados com sucesso na temperatura de 4°C por até 18 horas, sem ocasionar danos morfológicos aos folículos pré-antrais. Entretanto, na temperatura de 20°C, esses ovários só puderam ser estocados por seis horas.…”
Section: Discussionunclassified